ØªØ¹Ù„ÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒØªØ§Ø¨Ø© Ù„ØºÙŠØ±Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Badruzzaman Badruzzaman (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
Arabic has four skills are listening, speaking, reading and writing. Writing is a skill that requires a high level to practice continuously be accompanied with a high sense abilities. A culture of the earth shall awake relics sustainability if there that is written about the culture. Writing is an expression of human what is seen and felt. Writing skills in the Arabic language divided two: the first skill to write arabic letters and Arabic words correctly is called with intermediary skills (appliance) needed by the second skill, both the ability to write a sentence in accordance with the Arabic grammar. This article also tries to express the difficulties faced by non-Arabic speakers in Arabic writing, and also try to provide solutions to these difficulties.